2009
DOI: 10.1016/j.socscimed.2009.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Testing the influenza–tuberculosis selective mortality hypothesis with Union Army data

Abstract: Using Cox regression, this paper shows a weak association between having tuberculosis and dying from influenza among Union Army veterans in late nineteenth-century America. It has been suggested elsewhere [Noymer, A. and M. Garenne (2000). The 1918 influenza epidemic’s effects on sex differentials in mortality in the United States. Population and Development Review 26(3), 565–581.] that the 1918 influenza pandemic accelerated the decline of tuberculosis, by killing many people with tuberculosis. The question r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 50 publications
4
60
0
Order By: Relevance
“…Researchers have suggested ways to model frailty distributions, which might allow us to make better sense of observed aggregate mortality hazards (e.g., Aalen 1994;Steinsaltz and Wachter 2006;Vaupel and Carey 1993;Vaupel and Yashin 1985;Zahl 1997). Noymer (2009) suggests examining the interaction of different diseases as one way of studying the association between observed death rates and frailty distributions, as exposure to one disease can enhance mortality risk to another.…”
Section: Examination Of Frailty and Demographymentioning
confidence: 99%
“…Researchers have suggested ways to model frailty distributions, which might allow us to make better sense of observed aggregate mortality hazards (e.g., Aalen 1994;Steinsaltz and Wachter 2006;Vaupel and Carey 1993;Vaupel and Yashin 1985;Zahl 1997). Noymer (2009) suggests examining the interaction of different diseases as one way of studying the association between observed death rates and frailty distributions, as exposure to one disease can enhance mortality risk to another.…”
Section: Examination Of Frailty and Demographymentioning
confidence: 99%
“…Review of data from the 1918 influenza pandemic suggests that many individuals who died had active tuberculosis [14, 15] and that underlying tuberculosis infection may have contributed to the elevated mortality observed in young adults [15, 16]. However, limited data are available on excess mortality associated with seasonal influenza infection among patients with tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…I speculate the existence of other causal comorbidities among young adults. In support of this, an epidemiological study in the USA suggested that TB, which was more common among young adults in the early 20th Century than in the present day, may have been partly responsible for the high risk of death in this age group [46,47]. Other infectious diseases, most notably pneumococcal infection, are also known to worsen the clinical outcome of severe pneumonia attributed to influenza [48].…”
Section: Is the 2009 Pandemic Milder Than Spanish Influenza?mentioning
confidence: 96%